PERANAN SEKSI PENGENDALIAN DAN PENANGANAN SENGKETA HAK ATAS TANAH DI KABUPATEN NABIRE - salimubun, ahmad firmansyah; Simanjuntak, Kristi Warista; Lestaluhu, Rajab (Journal of Law Justice (JLJ), 2023)
The problem of land rights disputes must be handled properly and in its entirety so that the resolution is easy. The research in this article uses an empirical research focus. In writing, this research was carried out directly to the field with sociologists and interviews to understand what was being studied. By changing and describing the role of the Dispute Control and Handling Section in resolving land rights disputes, this research uses descriptive techniques in explaining it. Research results show that; (1) The Role of the Dispute Control and Handling Section at the Office of the National Land Agency in Nabire Regency. For 2020, especially for the period from August to November, there were 39 cases reported to the Dispute Management and Handling Section, approximately 25 cases were resolved through peaceful channels. The stipulation of Presidential Decree No. 26 of 1988 to review the position, duties and functions of the National Land Agency. (2) Land Rights Dispute Settlement Process at the Nabire Regency National Land Agency Office. As for the initial stages, the party that has the authority, the handling plan, legislation that can be applied, the final research plan is carried out to make a decision on the settlement of the case to be carried out, determining whether or not the application of the law is appropriate for the case being handled.